Analisis Wacana Jurnalisme Advokasi dalam Film Dokumenter Sexy Killers - Yusningtyas, Yusningtyas; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2019)
ABSTRACT Advocacy journalism seeks to provide other perspectives that are ignored by the media. Journalists have role to bring the voices of actors who do not have power to voice themselves in media. This journalism can be expressed as documentary film, such as indicated in Sexy Killers movie. Sexy Killers shows the struggle of the people who are affected by the existence of coal energy in Indonesia. The aim of this research is to describe how the application of advocacy journalism in Sexy Killers. This research used qualitative approach and was analyzed by using van Dijk discourse. Scenes of Sexy Killers were analyzed based on 6 elements of advocacy journalism. The results showed that Sexy Killers only practiced 5 out of 6 elements of advocacy journalism, that are focus of the news, issues raised, key informants, work priorities, and post-publication news expectations. Sexy Killers does not apply the principle of legality. Key Words: Advocacy Journalism, Discourse Analysis, Documentary Film, Sexy Killers